2004
DOI: 10.1111/j.1600-0501.2004.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Resonance frequency analysis of implants subjected to immediate or early functional occlusal loading

Abstract: Within the limitations of this study, it is concluded that failing implants show a continuous decrease of stability until failure. Low RFA levels after 1 and 2 months seem to indicate an increased risk for future failure. This information may be used to avoid implant failure in the future by unloading implants with decreasing degree of stability with time as diagnosed with the RFA technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
280
2
19

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(320 citation statements)
references
References 27 publications
11
280
2
19
Order By: Relevance
“…In a clinical study with bone graft in the maxilla, Rasmusson et al (13) reported an increase in ISQ values along the time, and recommended the use of small diameter drills for implant insertion, in order to generate high compression forces that allow higher stability, at least initially. Similarly, Glauser et al (14), in a study using RFA in 81 dental implants for a year, observed a continuous decrease of implant stability that finally failed. They concluded that low ISQ values after 1 to 2 months seem to indicate a higher risk for a future implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study with bone graft in the maxilla, Rasmusson et al (13) reported an increase in ISQ values along the time, and recommended the use of small diameter drills for implant insertion, in order to generate high compression forces that allow higher stability, at least initially. Similarly, Glauser et al (14), in a study using RFA in 81 dental implants for a year, observed a continuous decrease of implant stability that finally failed. They concluded that low ISQ values after 1 to 2 months seem to indicate a higher risk for a future implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…Glauser и соавт. [29] исследовали с использованием имплантатов MkVI Ti-Unite Brånemark («Nobel Biocare», Гетеборг, Швеция). 76% имплантатов были установлены в кость с маленькой плотностью и немедленно нагружались.…”
Section: стоматология 4 2016unclassified
“…Recent development of the Osstell TM machine that quantifies stability of the fixture using sound resonance 31 has helped to give the surgeon an objective measurement to determine treatment outcomes. Any micro-motion during the initial phases of bone healing will cause a lack of integration.…”
Section: Timing Of Loadingmentioning
confidence: 99%